The impact of insurance company participation on the capital market’s sustainable development—empirical evidence based on investor sentiment and stock price synchronicity - Hao, Fangjing; Li, Boyang; Yang, Juan (Frontiers in Environmental Science, 2022)
Given the representativeness and availability of data, this paper selects personal posts from the Oriental Wealth Internet Cafe and Sina Internet Cafe Forum to analyze the mechanism of insurance company participation, investor sentiment, and stock price synchronicity in China. Using a panel of data of listed companies from 2007 to 2018, evidence shows that investor sentiment in the stock market forum will increase the synchronicity of stock prices in the short term, while an insurance company’s shareholding effectively reduces the impact of investor sentiment on share price synchronicity which plays a mediator effect; the higher the proportion of the insurance company’s shareholdings, the more evident the effect. By conducting counterfactual research, the study found that insurance company participation can reduce the synchronicity of stock price by 0.10435 in a group with high investor sentiment than a group with low investor sentiment. For each investor sentiment group, the higher the proportion of the insurance company’s shareholdings, the greater the reduction in the synchronicity of stock prices. The results of this study can be used by national regulatory authorities to formulate policies in the field of e-finance in order to reduce stock price synchronization, stabilize financial markets, and minimize systemic financial risks.